Comparison of Quality and Ethanol Content of Liquid and Powder Kombucha from Jasmine Tea (Jasminum sambac L.) - Nisa Ihsani; Anisa Nurul Huda; Arifa Nadya Nur Afifah; Tiwi Sartika; Linda Pertiwi; Maelita Ramdani Moeis; Muhammad Farid Maksum; Aila Gema Safitri; Oktira Roka Aji (UIN Sunan Gunung Djati Bandung, 2025)
The fermentation process of kombucha has become a focus of halal product research due to its ethanol content. Processing kombucha into powder form can be an alternative to address the ethanol content in liquid kombucha, as it has undergone a drying process, making it a potential halal-certified functional drink. The objective of this study was to compare the quality of liquid and powdered kombucha. The research was conducted from March to September 2024 at the Biotechnology Laboratory, Muhammadiyah University of Bandung. The method used was the Complete Randomized Design (CRD) method. The parameters analyzed included ethanol content, total BAA (Bacterial Acetic Acid), pH, organic acid content, and sugar content. In the production of powdered kombucha, optimization of maltodextrin and gum arabic usage was also conducted to achieve the best solubility and taste. The best powdered kombucha was obtained with a maltodextrin-to-gum arabic ratio of 3:2. In the research, liquid kombucha contained ethanol at an average of 0.09%. In comparison, no ethanol was detected in the powdered kombucha (0%). Total BAA in powder decreased after the drying process (p<0.05). The pH value of kombucha in liquid form (4.4) also differed significantly from powdered (3.2) (p<0.05). However, the levels of organic acids and sugars in liquid and powdered kombucha did not differ significantly (p>0.05). The sugar content in liquid and powdered kombucha was lower than that in kombucha in general.